Developing a socio-economic framework for assessing the effectiveness of Expanded Public Works Programmes (EPWP): The case of the Prosopis mesquite Working for Water clearing project in the Northern Cape Province, South Africa - Ntsonge, Sinazo (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
The EPWP functions as a bridge between unemployment and entry into the labour market by providing work readiness skills training to its beneficiaries who receive below-market rate stipends for the short- term duration of their participation. The EPWP combines service delivery issues with social development objectives by promoting intensive manual labour in its projects. As a social protection strategy, public works programmes cater to those who do not meet the criteria to receive government social grants. As one of the programmes under the EPWP dealing with the control and eradication of invasive alien plants, the Working for Water (WfW) programme also uses intensive manual labour methods for clearing alien plant species. Although the clearing successes of WfW are well documented, the programme has focused little attention to the longer-term livelihood impacts of the temporary work and skills training provided to beneficiaries. This study suggests this could be due to a lack of the appropriate indicators to measure these outcomes. Therefore, an evaluation framework for environmental public works projects is proposed, which consists of outcome indicators to track the livelihood impact of the work experience and skills training on the beneficiaries post-participation, since the aim of these EPWP interventions is to improve beneficiaries' labour market outcomes. The Northern Cape province's Prosopis mesquite clearing project was used as the case study to develop and test the evaluation framework. The outcome indicators were informed by the key stakeholders' interviews and the beneficiaries' survey, specifically since the beneficiaries were well placed to give feedback on the benefits of the work experience and training post-participation. The combined strengths of the Sustainable Livelihoods Approach and the Capability Approach were useful for formulating the outcomes indicators, while the indicators for the inputs, activities and outputs were formulated from the key stakeholder interviews and online EPWP reports. A mixed methods approach was used and primary data were collected through key stakeholder interviews with the Prosopis mesquite clearing project managers and an online survey with some of the beneficiaries. Online EPWP reports and records obtained from WfW were used as secondary data. Data analysis used RStudio, Microsoft Excel and GraphPad Prism. The data analysis and evaluation framework indicators constituted the results section and aimed to highlight the factors that managers should focus on to achieve the desired livelihood outcomes. The proposed outcome indicators can be used to gauge the effectiveness of environmental public works' social development interventions. The results revealed that the project budget fluctuations resulted in the Working for Water managers adopting a myopic view in administering the workdays and skills training, which diminished the livelihood impact of the Prosopis mesquite clearing project to merely a 'make work' project with no observable longer-term livelihood benefits. The selection input indicators and their utilisation during project activities needs to be better aligned with the desired longer-term livelihood outcomes that these environmental public works projects seek to achieve, mainly that of preparing beneficiaries for jobs in the labour market.
Keywords: Public works -- South Africa Northern Cape Evaluation; Mesquite; South Africa. Expanded Public Works Programme; Working for Water Programme; Project management Case studies; Livelihood